Soil solution chemistry and impact of forest thinning in mountain forests in the Bavarian Alps - Bäumler, Rupert; et al. (Forest Ecology and Management, 1998)
The soil solution of two forested catchments in the Bavarian Alps was studied over a period of not quite four years with regard to the dynamics of solutes and the impact of forest thinning on the solution chemistry. Soil solution was obtained by porcelain tension cups from three depths (10, 30 and 50 cm). It is characterized by high concentrations of alkali and alkaline earth cations, and of silicate and bicarbonate. Solution chemistry in topsoil is influenced by atmospheric input, but the deposited acidity is almost completely and rapidly buffered through cation exchange and silicate weathering. The solution chemistry is further controlled by biogenetic processes including the release of ions by mineralization, and the temporary fixation of ions by biological immobilization and root uptake. Gaseous losses of N may occur due to a dominance of hydromorphic soils. Thinning (removal of 40% of the trees by thinning) caused strong changes of the solution chemistry. Except for silicate and sulfate the concentrations of all cations and anions increased mainly due to increased mineralization and the reduction of nutrient uptake by roots. Ammonium and nitrate showed the strongest effects. Solution chemistry returned to pre-event conditions one year after thinning due to the high buffer capacity of the soils.
UnivIS-Import:2015-03-05:Pub.1998.nat.dgeo.IG.profes_1.soilso
Keywords: Buffering processes; Forest thinning; Mineralization; Mountain forests; Soil solution